Digital Archiving Transformation at the Ministry of Religious Affairs: The Role of Communication Strategy, Modernization of the SRIKANDI System, and Bureaucratic Simplification - -, Ahmad Maulana; Dimas Artha Antariksa; Sudarmanti, Rini (KOMUNIDA : Media Komunikasi dan Dakwah, 2025)
This study aims to uncover how organizational communication strategies, the modernization of the Integrated Dynamic Archiving Information System (SRIKANDI), and bureaucratic simplification efforts interact to accelerate the digital transformation of records management at the Ministry of Religious Affairs of the Republic of Indonesia. Employing a qualitative approach, the research utilizes thematic analysis of secondary data processed through NVivo (mind maps, word clouds, and tree maps) and official documents, including the Secretary-General Circular Letter No. 31/2022 and SPBE implementation reports. The findings reveal that SRIKANDI successfully serves as a primary instrument for modernizing and simplifying archival bureaucracy by enhancing transparency, accountability, and efficiency in records management. However, its success heavily depends on multi-channel internal communication strategies and intensive employee training as key drivers of technology adoption. The primary challenges remain low human resource competencies, limited digital infrastructure, and weak inter-unit coordination. This study extends the UTAUT-2 model by integrating coercive isomorphism, demonstrating that in mandatory-use contexts, regulatory compliance is merely the initial stage, while true technology internalization is achieved only through intensive human-centered approaches. The research offers policy recommendations for other ministries and institutions in optimizing mandatory information systems and provides replicable best-practice models to support the national Electronic-Based Government System (SPBE).